The edge - Francis, Dick. (New York : Putnam, 1989)
Tor, undercover security operative for the British Jockey Club, masquerades as a waiter on a horse-racing junket called the Great Transcontinental Mystery Race Train.
Library Journal.
Wilson's Fiction.
Young Adult.
Young Adult
Keywords: Horse racing -- Canada -- Fiction; Mystery fiction; Railroads -- Fiction; Detective and mystery stories